(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:Iraq was distinguished by the phenomenon of political instability, as it was the cause of the emergence of some events that affected the security and stability of the country, including the (Farhoud) incident ( ) on the first of June 1941 between both Jews and Muslims, as the Jewish minority in Iraq during the period of monarchy is considered one of the important sects in the composition of Iraqi society. Hence the researcher’s interest in such a study, especially what accompanied this incident of looting and looting, and even reached the assault and killing between Jewish and Muslim citizens, which resulted in the fall of a number of wounded and dead, and the inability of the Iraqi government at that time to control the situation. Abdullah for the intervention of the British forces to control the situation, but the emergence of Abdullah al-Qassab and his position on the incident made him reject the intervention of the British forces in Iraqi issues, especially since they are internal issues, and this position in itself indicates the extent of his competence and policy in dealing with the situation, especially since he requested the intervention of the Iraqi army from In order to resolve issues and clashes. In order to clarify Abdullah Al-Qassab’s position in precise details, we must address the incident, mentioning the reasons and Abdullah Al-Qassab’s position on it.Keywords: Attitude - Butcher - Farhoud